The Effect of the Literacy Habituation Program on Students' Reading Interest - Septiyati Purwandari; Ainun Andriyani (Urecol Journal. Part A: Education and Training, 2022)
This study aims to determine the effect of the literacy habituation program on reading interest of fourth grade students at SD Negeri Kalisari, Mertoyudan District, Magelang Regency. This study uses the type of Pre-Experimental Design with the One Group Pretest Posttest Design model. The research subjects were selected using the Nonprobability Sampling saturated sampling model. The samples taken were 30 students. by using the data collection method in the form of observation tests. Data analysis used parametric statistical techniques, namely the Paired Sample t Test. The results showed that the results of the analysis of the paired sample t test had a significance value of 0.00 <0.05, meaning that there was a significant difference between the results of the pretest and posttest using the literacy habituation program. The results of this study can be concluded that the literacy habituation program affects the reading interest of fourth grade students at Kalisari Elementary School, Mertoyudan District.